Going beyond Security Community and Balance of Power: South America's Hybrid Regional Security Governance. Issue 4 (12th November 2021) - Villa, Rafael Duarte; Chagas-Bastos, Fabrício H; Braga, Camila de Macedo
Abstract: Regional security in South America cannot be explained simply by considering balance of power or security-community governance mechanisms. In this article, we present and discuss a hybrid security-governance approach for talking about governance security in the Americas, particularly, South America. We hypothesize that there exists a new security-governance configuration in which the traditional governance mechanisms—balance of power and security community—are not mutually exclusive, but overlap and coexist, leading to the emergence of a regional hybrid security architecture. Beyond explaining the reasons and causes for the overlap between security community and balance of power, we show the hybrid nature of regional security governance and point out how taking the hybridity conceptual approach fills the gaps within current research. We first offer a critique of two leading approaches to thinking about security in the Americas (balancing and security communities). Next, we show how the overlapping configurations in South America's regional security governance happen, testing Adler and Greve's (2009, "When Security Community Meets Balance of Power: Overlapping Regional Mechanisms of Security Governance." Review of International Studies 35[S1]: 59–84) framework against historical evidence. Last, we provide evidence of a hybrid security governance in the region. We complement our analysis with qualitative data from interviews with scholars, political, diplomatic, and military actors conducted in various countries across the region. Our contribution is a significant step toward understanding how security-governance formations come about in non-Western regions of the world, privileging its specificities. More importantly, we offer a novel angle to escape straitjacket hypotheses to security governance grounded in Western hegemonic ideal types, which have focus either on balance of power or on security-community models.